A CTNNB1‐altered medulloblastoma shows the immunophenotypic, DNA methylation and transcriptomic profiles of SHH‐activated, and not WNT‐activated, medulloblastoma. (30th March 2022) - Chiang, Jason; Moreira, Daniel C.; Pytel, Nicholas J.; Liu, Yen‐Chun; Blackburn, Patrick R.; Shi, Zonggao; Cardenas, Maria; Wheeler, David A.; Furtado, Larissa V.
Abstract: Recent advancements in molecular characterisation have identified four principal molecular groups of medulloblastoma: WNT, SHH, group 3 and group 4. Each has its characteristic clinical features, signature genetic alterations and distinct DNA methylome profiles. Thus far, CTNNB1 mutations have been considered pathognomonic of WNT‐activated medulloblastoma. Furthermore, it has been shown that CTNNB1 mutations dominantly drive the WNT‐activated phenotype in medulloblastoma, even in the presence of alterations in the SHH pathway. We herein report an illustrative case that challenges this belief—a medulloblastoma with a pathogenic CTNNB1 mutation that otherwise showed the histopathology, immunophenotype and methylation and transcriptomic profiles of an SHH‐activated medulloblastoma. Detailed molecular analyses, including whole exome sequencing, transcriptome analysis and DNA methylation profiling with DKFZ brain tumour classifier and St. Jude MLPnet neural network classifier analyses, have been performed on the tumour. Our example emphasises the diagnostic value of the immunohistochemistry panel with YAP1, GAB1 and β‐catenin and DNA methylation profiling, combined with exome sequencing, in the characterisation of medulloblastoma. CTNNB1 mutations are not specific for WNT‐activated medulloblastoma, and different CTNNB1 mutations have diverse oncogenic potential. Abstract : We herein report a medulloblastoma with a pathogenic CTNNB1 mutation that otherwise showed the histopathology, immunophenotype and methylation and transcriptomic profiles of an SHH‐activated medulloblastoma. Our example emphasises the diagnostic value of the immunohistochemistry panel with YAP1, GAB1 and β‐catenin and DNA methylation profiling, combined with exome sequencing, in the characterisation of medulloblastoma. CTNNB1 mutations are not specific for WNT‐activated medulloblastoma, and different CTNNB1 mutations have diverse oncogenic potential.